KONSEP PENGALAMAN KEAGAMAAN JOACHIM WACH - Triyani Pujiastuti (JURNAL ILMIAH SYI'AR, 2017)
This paper tries to expose Joachim Wach’s view of religious experience. Religious experience is a human activity in its existence with the creator. Religious experience arises when a person has practiced religious teachings so that they are inward and outward. The religious experience of one individual to another varies depending on how he practices his or her religion.